Protected Birds of Nepal: A Review of their Status, Distribution and Habitat - Baral, Hem S (The Initiation, 2010)
National Parks and Wildlife Conservation Act, 1973 is the major Act that forms the basis for biodiversity protection in Nepal. The Act lists nine species of birds protected by law. These species are Tragopan satyra (Satyr Tragopan), Lophophorus impejanus (Danphe), Catreus wallichi (Cheer), Buceros bicornis (Great Hornbill), Houbaropsis bengalensis (Bengal Florican), Sypheotides indica (Lesser Florican), Grus antigone (Sarus Crane), Ciconia ciconia (White Stork) and C. nigra (Black Stork). As these birds were listed on the Act several years back, there is a need to update the list taking into account the available information on Nepal's birds. Himalayan Nature funded by Critical Ecosystem Partnership Fund and World Wildlife Fund (WWF Nepal) is working to recommend updated list to Nepal government. Key Words: National Park and Wildlife Conservation Act, Protected birds of Nepal, Status update DOI: 10.3126/init.v3i0.2429 The Initiation Vol.3 2009 p.66-80